Analysis of Biochemical Composition of Honey and itsAnti-Oxidant,Phytochemicaland Anti-Bacterial Properties - Asaduzzaman, M (Journal of Biomedical and Pharmaceutical Research, 2017)
Honey mainly consists of sugars and water. Apart from sugars, honey also contains several vitamins especially B complex and vitamin C, together with a lot of minerals such as calcium, copper, iron, magnesium, manganese, phosphorus, potassium and zinc are also present. Honey has been used for its healing, nutritional and therapeutic properties since ancient times. Its antibacterial potentials even against multi-drug resistant bacteria, such as Staphylococcus aureus, Bacillus cereus, Bacillus subtillis, Escherichia coli, Staphylococcus albusand Shigellasonnei has been proved. The nutritional composition, minerals, antibacterial, and antioxidant properties of honey will be reviewed here. There is no available information on Biochemical and antioxidant properties on Bangladeshi honey, so we investigate honey for better understanding biochemical properties of honey. Honey samples were collected from the Sundarbon, Khulna, Bangladesh. The levels of PH, Moisture, Ash, Vitamins, minerals, and ascorbic acid, ascorbic acid equivalent antioxidant content (AEAC), sugar, protein, anti- microbial activity and antioxidants were determined in the honey samples using ferric reducing antioxidant power (FRAP), ABTS radical scavenging Activity and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assays. The total phenolic and flavonoid were determined by Folin-Ciocalteu and colorimetric assay method. The results of this study indicate that the samples compare favorably with samples in many parts of the world and also fall within the limits of international standards. This review covers the composition, physico-chemical properties and the most important uses of natural honey in human diseases. Keywords: Honey, Antioxidant, sugars, vitamin –c, minerals, Anti-bacterial properties.